1999
DOI: 10.1159/000029380
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Endothelin-1 Level in Chronic Obstructive Pulmonary Disease: Relationship with Natriuretic Peptide

Abstract: Background and Objective: Endothelin-1 (ET-1) is a potent vasoconstrictor peptide produced by the vascular endothelium. The purpose of this study was to elucidate the pathophysiological role of ET-1 in patients with pulmonary hypertension secondary to chronic obstructive pulmonary disease (COPD). Method: We measured plasma ET-1 levels during right heart catheterization both at rest and during exercise on room air and while breathing oxygen in patients with COPD. In addition, we simultaneously measured plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
3
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
1
27
3
2
Order By: Relevance
“…This result concurs with the results of recent studies [10, 11]. Fuji et al [12]also demonstrated that plasma ET-1 levels at rest were significantly higher in patients with COPD than in controls, and despite the progression of PH and desaturation with exercise, plasma ET-1 levels remained unchanged. In this study, plasma ET-1 levels were measured by right heart catheterization both at rest and during exercise in room air and on supplemental oxygen.…”
Section: Discussionsupporting
confidence: 91%
“…This result concurs with the results of recent studies [10, 11]. Fuji et al [12]also demonstrated that plasma ET-1 levels at rest were significantly higher in patients with COPD than in controls, and despite the progression of PH and desaturation with exercise, plasma ET-1 levels remained unchanged. In this study, plasma ET-1 levels were measured by right heart catheterization both at rest and during exercise in room air and on supplemental oxygen.…”
Section: Discussionsupporting
confidence: 91%
“…Tatsuo et al [59]found that plasma ET-1 levels were not affected by acute progression of hypoxia and pulmonary hypertension in COPD patients during exercise. Our patients had chronic and severe hypoxia and elevated ET-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…В ранее проведенных исследованиях показано увеличение концентрации BNP в плазме крови боль ных ЛГ, вызванной различными причинами [25][26][27][28], а также пациентов с систолической дисфункцией ПЖ [29], респираторной патологией [21,30]. В пред ставленном исследовании у больных ХОБЛ даже без признаков ЛГ концентрация BNP в плазме была вы ше по сравнению со значением этого показателя у лиц, не страдавших легочно сердечной патологи ей [31].…”
Section: Discussionunclassified
“…В пред ставленном исследовании у больных ХОБЛ даже без признаков ЛГ концентрация BNP в плазме была вы ше по сравнению со значением этого показателя у лиц, не страдавших легочно сердечной патологи ей [31]. Представляют интерес результаты ранее про веденных исследований, которые показали роль гипоксии [22,25,32,33], уровня эндотелина 1 [26], С реактивного белка [34], интерлейкина 6 [35] в по вышении концентрации BNP в плазме крови.…”
Section: Discussionunclassified